INTERFERENSI BAHASA INDONESIA PADA VIDEO TIKTOK @NADIATILEM “REAL TALK: KENAPA KOREA SELATAN LEBIH MAJU DARIPADA INDONESIA?” - Imania, Cahya Savitri; Kirani, Eka Dewi; Farah Mutia, Sabrina; Autar, Nayla (LPPM Universitas PGRI Silampari Lubuklinggau, 2024)
Abstract The purpose of this study is to describe Indonesian language interference in @Nadiatilem's Tiktok video which discusses